Rhizosphere-associated soil microbiome variability in Verticillium wilt-affected Cotinus coggygria - Zhao, Juan; Cheng, Yanli; Jiang, Nan; Qiao, Guanghang; Qin, Wentao (Frontiers in Microbiology, 2024)
Verticillium wilt is the most devastating soil-borne disease affecting Cotinus coggygria in the progress of urban landscape construction in China. To assess the variability of the rhizosphere associated soil microbiome in response to Verticillium wilt occurrence, we investigated the microbial diversity, taxonomic composition, biomarker species, and co-occurence network of the rhizosphere associated soil in Verticillium wilt affected C. coggygria. The alpha diversity indices of the rhizosphere bacteria in Verticillium wilt affected plants showed no significant variability compared with those in healthy plants, except for moderate increase of Shannon and Invsimpson indices, while the fungal alpha diversity indices were significantly decreased. The abundance of certain dominant or crucial microbial taxa, such as Arthrobacter, Bacillus, Streptomyces, and Trichoderma, displayed significant variations among different soil samples. The bacterial and fungal community structure exhibited distinct variability, as evidenced by the Bray-Curtis dissimilarity matrices. Co-occurrence networks unveiled intricate interactions within the microbial community of Verticillium wilt affected C. coggygria, with greater edge numbers and higher network density. The phenomenon was more evident in the fungal community, showing increased positive interaction, which may be associated with the aggravation of Verticillium wilt with the aid of Fusarium. The proportions of bacteria involved in membrane transport and second metabolites biosynthesis functions were significantly enriched in the diseased rhizosphere soil samples. These findings suggested that healthy C. coggygria harbored obviously higher abundance of beneficial microbial consortia, such as Bacillus; while Verticillium wilt affected plants may recruit antagonistic members like Streptomyces in response to Verticillium dahliae infection.This study provides a theoretical basis for understanding the soil micro-ecological mechanism of Verticillium wilt occurrence, which may be helpful in prevention and control of the disease in C. coggygria from the microbiome perspective.